Pengaruh Prenatal Care Yoga terhadap Pengurangan Keluhan Ketidaknyamanan Ibu Hamil Trimester III di Puskesmas Putri AyuKota Jambi - Gustina Gustina; Nurbaiti Nurbaiti (Universitas Baiturrahim, 2020)
AbstractDuring pregnancy changes will occur in the entire body system of the mother both physically and psychologically, although physiological but if not understood by the mother and not treated will be able to make discomfort very disturbing during the process of pregnancy, childbirth and the puerperium, Prenatal Care Yoga is expected to help in dealing with discomfort during pregnancy, especially the third trimester of pregnancy Putri Ayu Health Center has provided pregnancy exercise services but has never given prenatal care yoga, due to the absence of trained staff at the Puskesmas, the researchers chose Puskesmas Putri Ayu as a research site. Intervene prenatal care yoga with quasi experimental one group pre-post-test design method. affordable population of 301 people visits K4 pregnant women to the Putri Ayu health center. he sample of purposive sampling was 32 people. The subject was carried out pre test and post test in the form discomfort questionnaire using a comparative scale of pain. Prenatal care yoga 4 times for 4 consecutive weeks Most of the third stage discomfort was pre-test, 21 (65.6%), post-test to 15 (46.9) there was an effect of prenatal care yoga on reducing complaints of discomfort of third trimester pregnant women with a p-value <0,000 (95% CI).